Responses of a hot spring cyanobacterium under ultraviolet and photosynthetically active radiation: photosynthetic performance, antioxidative enzymes, mycosporine-like amino acid profiling and its antioxidative potentials - Ahmed, Haseen; Pathak, Jainendra; Rajneesh; Sonkar, Piyush K.; Ganesan, Vellaichamy; Häder, Donat-Peter; Sinha, Rajeshwar P. (3 Biotech, 2021)
This study summarizes the response of a hot spring cyanobacterium Fischerella sp. strain HKAR-14, under simulated light conditions of ultraviolet radiation (UVR), photosynthetically active radiation (PAR), PAR+UV-A (PA) and PAR+UV-A+UV-B (PAB). Exposure to UVR caused a decline in growth and Chl a while total carotene content increased under PA and PAB. Maximum photochemical efficiency of photosystem II (F-v/F-m) and relative electron transport rate decreased significantly in PA and PAB exposure. Higher non-photochemical quenching and lower photochemical quenching values were observed in UVR-exposed samples as compared to the control. Levels of intracellular reactive oxygen species (ROS) increased significantly in PAB and PA. Fluorescence microscopic images showed an increase in green fluorescence, indicating the generation of ROS in UVR. The antioxidant machinery including superoxide dismutase, catalase and peroxidase showed an increase of 1.76-fold and 2.5-fold superoxide dismutase, 2.4-fold and 3.7-fold catalase, 1.83-fold and 2.5-fold peroxidase activities under PA and PAB, respectively. High-performance liquid chromatography equipped with photodiode array detector, electrospray ionization mass spectrometry, Fourier-transform infrared spectroscopy and nuclear magnetic resonance spectroscopy analyses reveal the occurrence of a single mycosporine-like amino acid, shinorine (lambda (max) 332.3 +/- 2 nm, m/z 333.1), with a retention time of 1.157 min. The electrochemical characterization of shinorine was determined by cyclic voltammetry. The shinorine molecule possesses electrochemical activity and represents diffusion-controlled process in 0.1 M (pH 7.0) phosphate buffer. An antioxidant assay of shinorine showed its efficient activity as antioxidant which increased in a dose-dependent manner.
CRIS-Team WoS Importer:2021-02-05